Liver Proteomics: Methods and Protocols - Josić, Djuro (Methods in molecular biology, 2012)
The liver is responsible for a wide range of critical functions essential to life, and is composed of several different cell types. In Liver Proteomics: Methods and Protocols, expert researchers in the field detail many of the methods that are used to study the live. These methods include the most up-to-date strategies being used to characterize the liver proteome at the global, cellular, subcellular, post translational and functional level.Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Liver Proteomics: Methods and Protocols seeks to aid scientists in the further study of this crucially important organ.
Keywords: Aufsatzsammlung; Molekularbiologische Methode; Proteomanalyse; Leber